2001
DOI: 10.1046/j.1365-2141.2001.02620.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo platelet activation in atherothrombotic stroke is not determined by polymorphisms of human platelet glycoprotein IIIa or Ib

Abstract: Summary. Platelet membrane glycoprotein polymorphisms are candidate risk factors for thrombosis, but epidemiological data are conflicting. Thus, demonstration of a genotype-dependent alteration in function is desirable to resolve these inconsistencies. We investigated in vivo platelet activation in acute thrombosis and related this to platelet genotype. Frequencies of the 1b and 2b alleles of the HPA 1a/1b and HPA 2a/2b platelet glycoprotein polymorphisms were determined in 150 (52 men/98 women, mean age 58´3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 55 publications
4
29
0
1
Order By: Relevance
“…38 However, other studies failed to demonstrate an association between HPA1a/b and ischemic stroke. 25,37 These conflicting results obtained from various studies can stem from differences in the studied populations and from different specific outcomes that were measured.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…38 However, other studies failed to demonstrate an association between HPA1a/b and ischemic stroke. 25,37 These conflicting results obtained from various studies can stem from differences in the studied populations and from different specific outcomes that were measured.…”
Section: Discussionmentioning
confidence: 86%
“…32,33 A polymorphism in the GP IIIa gene (a single nucleotide change T/C, which causes Leu33Pro transition) has also been associated with coronary artery disease in some studies 34 -36 but not in patients with stroke. 26,27,[35][36][37][38] The aim of the present study was to evaluate whether the development of stroke or TIA in patients with significant (Ն50%) carotid artery stenosis is associated with inherited or acquired thrombophilic factors and/or platelet GP polymorphisms.…”
mentioning
confidence: 99%
“…Recent studies [10, 21, 22] have demonstrated that persistent increased platelet activation in stroke patients can, in part, be the result of chronic inflammatory processes [23], vascular risk factors [24], diffuse atherosclerotic lesions [24] or the extent of vascular damage due to a stroke [10]. Interestingly, two recent studies have further demonstrated that substantial interindividual variability is present in platelet reactivity to activation of glycoprotein IIb/IIIa in response to a low concentration of ADP [25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Platelets are activated in the early, (Grau et al, 1998;Meiklejohn et al, 2001;Marquardt et al, 2002;Garlichs et al, 2003;McCabe et al, 2004a) subacute, (Marquardt et al, 2002) and late phases (Grau et al, 1998;Meiklejohn et al, 2001;Garlichs et al, 2003;McCabe et al, 2004a) after transient ischaemic attack (TIA) or ischaemic stroke. Consequently, antiplatelet agents have the potential to play a key role in the secondary prevention of vascular events in patients with ischaemic cerebrovascular disease (CVD).…”
mentioning
confidence: 99%